2014
DOI: 10.1371/journal.pone.0093495
|View full text |Cite
|
Sign up to set email alerts
|

Waggle Dance Distances as Integrative Indicators of Seasonal Foraging Challenges

Abstract: Even as demand for their services increases, honey bees (Apis mellifera) and other pollinating insects continue to decline in Europe and North America. Honey bees face many challenges, including an issue generally affecting wildlife: landscape changes have reduced flower-rich areas. One way to help is therefore to supplement with flowers, but when would this be most beneficial? We use the waggle dance, a unique behaviour in which a successful forager communicates to nestmates the location of visited flowers, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
233
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 180 publications
(250 citation statements)
references
References 42 publications
14
233
3
Order By: Relevance
“…From a variety of methods, it is known that honeybees will forage as far as c. 10-12 km from the hive (Beekman & Ratnieks, 2000;Ratnieks, 2007). But previous research that decoded honeybee waggle dances has shown that the actual foraging distances of honeybees in spring in the Brighton area are well below this maximum range with a median of 647 m, interquartile range of 364-1305 m, and with 95% of foraging within 2114 m (Couvillon, Schürch, & Ratnieks, 2014b;Garbuzov, Schürch, & Ratnieks, 2014). Other studies confirm that foraging distances in spring Figure 2.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…From a variety of methods, it is known that honeybees will forage as far as c. 10-12 km from the hive (Beekman & Ratnieks, 2000;Ratnieks, 2007). But previous research that decoded honeybee waggle dances has shown that the actual foraging distances of honeybees in spring in the Brighton area are well below this maximum range with a median of 647 m, interquartile range of 364-1305 m, and with 95% of foraging within 2114 m (Couvillon, Schürch, & Ratnieks, 2014b;Garbuzov, Schürch, & Ratnieks, 2014). Other studies confirm that foraging distances in spring Figure 2.…”
Section: Resultsmentioning
confidence: 92%
“…Whiskers extend to the extreme value or 1.5 times the interquartile range, whichever is lower. The lower horizontal dashed line is the median spring honeybee foraging distance (647 m) and the upper horizontal dashed line is the 95%-quantile (2114 m) from published data on honeybees in the South East study area (Couvillon et al, 2014b). Additionally, the numbers given at the intersection of each box with these lines give the exact percentages of random points within the median and 95%-quantile spring foraging distance, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bees were trained to feeders 1 m or 100 m away from the focal colony. Honeybees usually forage and recruit for natural food at much greater distances (Couvillon, Schürch, & Ratnieks, 2014;Waddington, Herbert, Visscher, & Richter, 1994), but we chose these distances because 100 m was the furthest distance to which we could reliably train bees for all the tested sucrose concentrations.…”
Section: General Methodsmentioning
confidence: 99%
“…Our results suggest that recruitment dancing decisions depend upon interactions between predation risk and cost of travel. However, honeybees typically forage over distances of more than 100 m (Couvillon et al, 2014) and future studies examining the effect of attacks at much greater distances would be beneficial.…”
Section: Effects On Recruitment Dancingmentioning
confidence: 99%